Phosphate adsorption from aqueous solution using electrospun cellulose acetate nanofiber membrane modified with graphene oxide/sodium dodecyl sulphate - Amin, N. A. A. M. (MDPI AG, 2021)
Eutrophication and water pollution caused by a high concentration of phosphate are two concerning issues that affect water quality worldwide. A novel cellulose-based adsorbent, cellulose acetate/graphene oxide/sodium dodecyl sulphate (CA/GO/SDS), was developed for water treatment. A 13% CA solution in a mixture of acetone:dimethylacetamide (2:1) has been electrospun and complexed with a GO/SDS solution. The field emission scanning electron microscope (FESEM) showed that the CA membrane was pure white, while the CA/GO/SDS membrane was not as white as CA and its colour became darker as the GO content increased. The process of phosphate removal from the solutions was found to be aided by the hydroxyl groups on the surface of the CA modified with GO/SDS, as shown by infrared spectroscopy. An optimization condition for the adsorption process was studied by varying pH, immersion time, and the mass of the membrane. The experimental results from phosphate adsorption showed that CA/GO/SDS had an excellent pH adaptability, with an optimum pH of 7, and maximum removal (>87.0%) was observed with a membrane mass of 0.05 g at an initial concentration of 25 mg L−1 . A kinetic study revealed that 180 min of contact time could adsorb about 87.2% of phosphate onto the CA/GO/SDS membrane. A typical pseudo-second-order kinetic model successfully portrayed the kinetic sorption of phosphate, and the adsorption equilibrium data were well-correlated with the Langmuir adsorption model, suggesting the monolayer coverage of adsorbed molecules.